Synthesis and electromagnetic characterization of polycaprolactone filled with hematite and OPEFB fiber nanocomposite - Mensah, Ebenezer Ekow (2019)
The most common materials used for microwave absorbing applications are ferrites. However, ferrites are expensive, heavy, non – biodegradable and have low dielectric loss properties especially at high frequencies. This study presents the development of novel composites using recycled ferrite in conjunction with biodegradable oil palm empty fruit bunch (OPEFB) fiber and polycaprolactone (PCL) as an alternative for reducing the limitations of ferrite – based microwave absorbing materials. Hematite (α – Fe2O3) was recycled from mill scale waste (steel waste) material and the particle sizes reduced to nanosize after several hours of high energy ball milling (HEBM). The relationship between the reduced particle sizes and the dielectric properties was then determined. α – Fe2O3/PCL and α – Fe2O3/OPEFB fiber/PCL nanocomposites with different loadings (5 to 25%) of 16.2 nm α – Fe2O3 nanofiller were fabricated and characterized for their dielectric, magnetic and microwave absorption properties. The material composition and structural properties were analyzed using X – ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X – ray spectroscopy (EDX), high resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR) and Brunauer – Emmett – Teller (BET) techniques. The relative complex permittivity and permeability of the samples were respectively measured using the open – ended coaxial probe and the rectangular waveguide techniques while the microwave absorption properties were measured with the microstrip at 1 GHz to 4 GHz. The results showed that the relative complex permittivity of the recycled α – Fe2O3 increased with reduced particle size. The dielectric loss factor (ɛ'') increased from 0.17 to 0.46 when the particle size was reduced from 1.73 μm to 16.2 nm at 8 GHz. Within the X – band (8 GHz – 12 GHz) frequency range, the relative complex permittivity properties of the recycled α – Fe2O3 particles were higher as compared to a commercial α – Fe2O3 (Alfa Aesar). Additionally, the relative complex permittivity (ε*) values of the nanocomposites increased with recycled α – Fe2O3 nanofiller content and were higher in the α– Fe2O3/OPEFB/PCL nanocomposites than the α – Fe2O3/PCL nanocomposites. This is due to the high loss factor of the incorporated OPEFB fiber. Attenuation and power loss due to absorption equally increased with recycled α – Fe2O3 nanofiller loadings. At 2.4 GHz, the range of attenuation for the α– Fe2O3/OPEFB/PCL nanocomposites was from 2 dB to 2.6 dB while the power loss values were from 15 dB to 17.3 dB. The attenuation values for the α – Fe2O3/PCL nanocomposites were however from 1.8 dB to 2 dB while the power loss values were in the range of 13.6 dB to 15.2 dB. The recycled α–Fe2O3/OPEFB/PCL nanocomposites can therefore serve as promising alternatives for microwave absorbing applications in the 1 – 4 GHz in view of their low cost, low density, biodegradability and attractive absorption behaviour. Recycled hematite at reduced particle size has the potential for use as a filler in other polymeric composites and its application can reduce the cost of ferrite – based microwave absorbing materials significantly without compromising the absorption efficiency of the materials.